Studi Kasus Konsentrasi Belajar Anak ADHD di PAUD Putra Harapan: Subjek Anak ADHD - Rosidah, Wahyuningsih; Fauzi, Fauzi; Mardhiyah, Layla (Lentera: Jurnal Ilmiah Kependidikan, 2025)
ADHD children are children who have difficulty concentrating, have difficulty sitting, and have more physical motor skills. This is proven by some research. Concentration of learning is something that is owned by individuals but we do not know. ADHD children's learning concentration cannot last as long as other normal children, normal children may be able to hold sitting for about five minutes but ADHD children cannot at most 2-3 minutes the child can hold sitting. The concentration of learning is also different, ADHD children are easily bored in learning. This research method uses qualitative with case studies. The population of this study were two ADHD children and teachers. The results of this study are that the first subject, GS, has severe ADHD, his learning concentration is very sufficient, the stimulus given by the teacher to him is difficult for him to accept. While the second subject, AR, is a mild ADHD child, in his learning concentration AR is very good. AR does have difficulty in concentrating but when the teacher provides motivation and invitation to learn he always wants to.